AL-FARABI: PHILOSOPHY OF EMANATION, GODHEAD, PROPHETHOOD, SOUL AND INTELLECT - Syofrianisda, Syofrianisda; AM, Rusydi; Saputra, Riki; Murni, Dewi (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2024)
The issue that is still under long debate is the problem of the universe, which reaps the pros and cons associated with the concept of emanation. This paper intends to examine al-Farabi's opinion on the concept of emanation associated with the concept of the creation of the universe. This research is a type of library research, namely researching using documents from existing literature sources to help find the data being analyzed. Based on this study, it appears that the concept of emanation pioneered by al-Farabi is in accordance with the Big Bag theory. In the concept of emanation, the influence of neo-platonism metaphysical philosophy is very visible. Al-Farabi argues that the Prophet, Philosopher, and King are a unity of meaning despite having different approaches.